(3eNJUQ efGbH GdEeGe CMeO Hf MfHds - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s ((3EHQGgje Hf YHO Gddg GdebOSi GdPfGHi s)
(3ChdgG (B:s
(3HMeO Gddg fHJOi UGdM Hf CMeO jbhd (B: (3hdO , jYfi CHGg , SfI CQHY hSJjf heGFI ai QHjY GdChd s
(3BNQgG (B:s
(3hdh PgHfG fPcQ ai cd WHbI LejY CYjGfgG Ch GSJbUjfG CNHGQ GdePchQjf dWGd cJGHfG ; dCffG GbJUQfG Ydi CYjGf GdCYjGf ef cd WHbI BNQ GdcJGH s
(3hgj eNWhWI fGOQIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs